PENGARUH KARAKTERISTIK DEWAN KOMISARIS TERHADAP KINERJA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fahmi Fajrianto; Aditya Septiani (Diponegoro Journal of Accounting, 2016)
This study aims to examine the effect of board director’s characteristics  of firm performance. The purpose of this study is to provide empirically evidence about the effect of board director’s characteristics of firm performance. The independent variables of this study are board ownership, board size, board independence, and gender diversity . Board characteristics measured by disclosure showed in annual report. Firm performance measured by ALTMAN Z-Score which consisted by data acquired from disclosure showed in annual report. The population in this study are 418companies which listed on Indonesian Stock Exchange in the period of 2013. Sample were selected by purposive sampling method and finally obtained 259 companies that fulfill the criteria. Data were analyzed using multiple regression analysis model.The result show that board size significantly positive to firm performance, meanwhile managerial ownership, board independence, and gender diversity are not significantly positive. Based on the result, conclude that board size will take action of responsibility besides making profit from the firm.